2021
DOI: 10.1111/php.13402
|View full text |Cite
|
Sign up to set email alerts
|

A Need to Revise Human Exposure Limits for Ultraviolet UV‐C Radiation

Abstract: The COVID-19 pandemic has greatly heightened interest in ultraviolet germicidal irradiation (UVGI) as an important intervention strategy to disinfect air in medical treatment facilities and public indoor spaces. However, a major drawback of UVGI is the challenge posed by assuring safe installation of potentially hazardous short-wavelength (UV-C) ultraviolet lamps. Questions have arisen regarding what appear to be unusually conservative exposure limit values in the UV-C spectral band between 180 and 280 nm. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Miniaturized UV sensors can be employed to monitor hazardous exposures during working activities involving artificial sources of radiation without interfering with normal activities [160,161]. Some industrial applications, such as sterilization processes, rely on the use of highly damaging UV-C radiation, necessitating wearable devices that can reliably detect and quantify any accidental exposure to workers [162]. In addition, an enhanced UV-sensing system would be useful to detect small amounts of incoming UV-C radiation and to correlate these measurements with ozone layer depletion, particularly in regions that are most at risk, such as those near the equator.…”
Section: Applications Of Gpns In Environmental Monitoring: Uv Radiati...mentioning
confidence: 99%
“…Miniaturized UV sensors can be employed to monitor hazardous exposures during working activities involving artificial sources of radiation without interfering with normal activities [160,161]. Some industrial applications, such as sterilization processes, rely on the use of highly damaging UV-C radiation, necessitating wearable devices that can reliably detect and quantify any accidental exposure to workers [162]. In addition, an enhanced UV-sensing system would be useful to detect small amounts of incoming UV-C radiation and to correlate these measurements with ozone layer depletion, particularly in regions that are most at risk, such as those near the equator.…”
Section: Applications Of Gpns In Environmental Monitoring: Uv Radiati...mentioning
confidence: 99%
“…In addition, while there might be ongoing concerns regarding exposure to UV for occupants, recent research and studies indicated that the risk is within the current bands of acceptability because specially designed lamp fixtures ensure that occupants will only be exposed indirectly to low UV-c intensities under a threshold limit value [ 145 ]. Some researchers even hold that the current threshold is “overly conservative” and has degraded the efficacy of upper-room UVGI intervention based on experimental evidence [ 145 , 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is hope that this effect is not cumulative, as epithelial shedding may provide added protection, this has not yet been tested, to the best of our knowledge. There has also been very little testing on humans-although one author exposed their eye briefly and informally and reported only mild irritation [139]. There has also been little consideration for variations like dry eyes, which may remove a critical protective barrier; cuts or abrasion of the skin, which may remove protective dead skin cells; or exposure to other sensitive areas.…”
Section: Radiation Safety Considerationsmentioning
confidence: 99%